Considering potential seismic sources in earthquake hazard assessment for Northern Iran - Abdollahzadeh, Gholamreza; Sazjini, Mohammad; Shahaky, Mohsen; Tajrishi, Fatemeh Zahedi; Khanmohammadi, Leila (Springer, 2014)
Located on the Alpine-Himalayan earthquake belt, Iran is one of the seismically active regions of the world. Northern Iran, south of Caspian Basin, a hazardous subduction zone, is a densely populated and developing area of the country. Historical and instrumental documented seismicity indicates the occurrence of severe earthquakes leading to many deaths and large losses in the region. With growth of seismological and tectonic data, updated seismic hazard assessment is a worthwhile issue in emergency management programs and long-term developing plans in urban and rural areas of this region. In the present study, being armed with up-to-date information required for seismic hazard assessment including geological data and active tectonic setting for thorough investigation of the active and potential seismogenic sources, and historical and instrumental events for compiling the earthquake catalogue, probabilistic seismic hazard assessment is carried out for the region using three recent ground motion prediction equations. The logic tree method is utilized to capture epistemic uncertainty of the seismic hazard assessment in delineation of the seismic sources and selection of attenuation relations. The results are compared to a recent practice in code-prescribed seismic hazard of the region and are discussed in detail to explore their variation in each branch of logic tree approach. Also, seismic hazard maps of peak ground acceleration in rock site for 475- and 2,475-year return periods are provided for the region.
Keywords: Probabilistic seismic hazard assessment; Seismic sources; Earthquake catalogue; Logic tree technique